Altered intrinsic and network properties of neocortical neurons in the Ts65Dn mouse model of Down syndrome. Issue 12 (23rd December 2015) - Cramer, Nathan P.; Xu, Xiufen; F. Haydar, Tarik; Galdzicki, Zygmunt
Abstract: All individuals with Down syndrome (DS) have a varying but significant degree of cognitive disability. Although hippocampal deficits clearly play an important role, behavioral studies also suggest that deficits within the neocortex contribute to somatosensory deficits and impaired cognition in DS. Using thalamocortical slices from the Ts65Dn mouse model of DS, we investigated the intrinsic and network properties of regular spiking neurons within layer 4 of the somatosensory cortex. In these neurons, the membrane capacitance was increased and specific membrane resistance decreased in slices from Ts65Dn mice. Examination of combined active and passive membrane properties suggests that trisomic layer 4 neurons are less excitable than those from euploid mice. The frequencies of excitatory and inhibitory spontaneous synaptic activities were also reduced in Ts65Dn neurons. With respect to network activity, spontaneous network oscillations (Up states) were shorter and less numerous in the neocortex from Ts65Dn mice when compared to euploid. Up states evoked by electrical stimulation of the ventrobasal nucleus (VBN) of the thalamus were similarly affected in Ts65Dn mice. Additionally, monosynaptic EPSCs and polysynaptic IPSCs evoked by VBN stimulation were significantly delayed in layer 4 regular spiking neurons from Ts65Dn mice. These results indicate that, in the Ts65Dn model of DS, the overall electrophysiological properties of neocortical neurons are altered leading to aberrant network activity within the neocortex. Similar changes in DS individuals may contribute to sensory and cognitive dysfunction and therefore may implicate new targets for cognitive therapies in this developmental disorder. Abstract : Spontaneous synaptic events and coordinated network activity are less frequent in the somatosensory cortex of 2–3 week old Ts65Dn mice, the most studied mouse model of Down syndrome. Abnormal network activity combined with a decreased specific membrane resistance of layer 4 neurons suggests that information flow through the neocortex is impaired in these mice. Such changes, if present in the neocortex of Down syndrome individuals may impact their cognitive abilities.